(untitled) (Journal of the College of Basic Education, 2024)
The current research aimed to identify the aspects of ingenuity among gifted children with learning difficulties from the point of view of their parents, to achieve the goal of the study, the descriptive approach was adopted, and a research tool was built consisting of a measure of the aspects of ingenuity among gifted children with learning difficulties in Iraq, and it was answered by Parents. The scale included (30) items distributed over three areas: (cognitive, social, and technological), with (10) items for each area. The research sample consisted of (112) gifted people with learning difficulties whose answers were obtained through their parents. The psychometric properties of the ambidexterity aspects scale were extracted, represented by validity, which was extracted in two ways, namely face validity and construct validity, and reliability, which was extracted in two ways: the re-test method and amounted to (0.91), and by the Vacronbach equation method and amounted to (0.87), and it was concluded that there are aspects of ambidexterity. Among gifted people with learning difficulties, and in light of the research results, the researcher concluded a set of suggestions and recommendations.